'I need to get some details first': Record keeping as a potential barrier to effective complaint-call management. Issue 1 (1st February 2016) - Weatherall, Ann
Abstract : In this article, I examine audio recordings of telephone calls to an independent dispute resolution service in which customers complained about their electricity, gas or water providers. Part of the job of the intake officers (who answer the calls) is to enter relevant information about the caller and the complaint into a computer software system called RESOLVE. A dataset of 120 calls were analysed using conversation analysis. Although there was no fixed order for registering caller and complaint details, intake officers regularly prioritised registering caller details. Sometimes that meant interrupting callers as they were describing their problem. On the whole, callers who were interrupted co-operated with the intake officer, but an analysis of a call is presented where the caller did not co-operate. The findings support a recommendation for flexibility in the order of activities that achieve telephone-mediated dispute resolution. Being flexible is most likely to effectively progress the interaction to accomplish the institution's business in this case. Flexibility may be a general principle for the delivery of an effective dispute resolution service.